Penerapan Multimedia dalam Pembelajaran bagi Guru di TK Aisyiyah Ranting Parangtambung - Veronika Asri Tandirerung; Hasanah Hasanah (Universitas Negeri Makassar, 2019)
The community partnership program implemented in Aisyiyah Kindergarten aimed to improve thecompetence of kindergarten teachers in the application of multimedia learning. The existence of technologicalchanges, as well as changes in student generation are of concern to all educators so that they can also improve andchange the learning model that has been applied. The activities applied to improve the competence of teachers inAisyiyah Kindergarten were: a) Trainedthe Kindergarten teachers to find out the method of using ICT in learning; b)Trainedthe teacher groups to skillfully plan ICT-based learning for PAUD children. The activity was conducted inManuruki Street, Tamalate District. The implementation methods used were the lecture method and practice. Theteachers were given knowledge about learning models for millennial generations and the Alpha generation.Furthermore, they were offered practical activities, including making slide presentations in Microsoft power pointand creating the media for audio video providers, namely media-based website or youtube.com. The observationresults of the program implementation showed high interest of teachers to learn and actively ask questions in thetraining process. Thus, this community service partnership program could help in improving the quality of thelearning process.